THE ROLE OF THE GOVERNMENT IN IMPROVING THE PERFORMANCE OF MSMES IN INDONESIA DURING THE COVID-19 PANDEMIC - Mega Aulianda; Sudarmiatin Sudarmiatin; Agus Hermawan (Universitas PGRI Madiun, 2022)
The Covid-19 pandemic has a tremendous impact on the economy. Last year the whole world faced an economic downturn and caused a very deep contraction as almost all countries imposed strict mobility restrictions. Many countries have implemented lockdowns which have consequences for the economy which immediately slumped very sharply. Indonesia is faced with many problems related to economic aspects as a result of Covid-19. The economics Indonesia in 2020 experienced negative growth, unemployment and poverty rates increased. Based on Year on Year calculations, economic growth in the first quarter of 2020 showed a weakening by only reaching 2.97% compared to the achievement of the first quarter of 2019 which was 5.07%. The research method uses the document study method on the results of previous research, which is traced through journals on several electronic media such as digital libraries, websites and library journal connections. Journal searches are carried out via Google Browser and Google Scholar. Journal searches are carried out using keywords: MSMEs, the role of the Indonesian government in the economy, the economy of the covid 19 pandemic. From each research result obtained, it is further analyzed, which is then used as a supporting journal to strengthen that the Indonesian government plays a role in improving performance of micro, small and medium enterprises. The Indonesian government has a perpu in terms of handling micro, small and medium enterprises in Indonesia; The Perppu regulates state financial policies including state revenue policies including policies in the field of taxation, state expenditure policies including policies in regional finance, and financing policies; The government allows MSME business activities to be a guarantee for accessing business financing loans; the government also provides a Special Allocation Fund (DAK) to support the empowerment and development of MSMEs.